Komunikasi Persuasif Puskesmas dalam Menyosialisasikan Protokol Kesehatan Selama Masa Pandemi Covid-19 di Desa Pantai Cermin Kecamatan Tanjung Pura - Nurhafiza, Nurhafiza; Maraimbang; Yusra Dewi Siregar (IAI Nasional Laa Roiba Bogor, 2024)
Community Health Centers are a means for the government to provide information about matters and developments regarding Covid-19 as well as health protocols for preventing it. Judging from persuasive communication or communication carried out by inviting or persuading communicants, how does the Community Health Center actually persuade or invite the public to comply with health protocols in accordance with government directives? The approach used in this study is a qualitative approach. A qualitative approach is an approach that is able to provide clear and structured ideas or images. This research resulted that the Pantai Cermin Community Health Center, Tanjung Pura District, the application of persuasive communication in socializing the Covid-19 Pandemic Health Protocol by increasing public awareness and health in Pantai Cermin Village became a determinant for increasing public awareness about the importance of maintaining health and immunity for children and the elderly. and the elderly so they can avoid the dangers of the Covid-19 virus.